2005
DOI: 10.1371/journal.pmed.0020133
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the “Diseases of Affluence” Paradigm: Global Patterns of Nutritional Risks in Relation to Economic Development

Abstract: BackgroundCardiovascular diseases and their nutritional risk factors—including overweight and obesity, elevated blood pressure, and cholesterol—are among the leading causes of global mortality and morbidity, and have been predicted to rise with economic development.Methods and FindingsWe examined age-standardized mean population levels of body mass index (BMI), systolic blood pressure, and total cholesterol in relation to national income, food share of household expenditure, and urbanization in a cross-country… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
296
1
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(322 citation statements)
references
References 50 publications
16
296
1
9
Order By: Relevance
“…A recent study has also demonstrated the potential of remote sensed and meteorological data products as being reliable representation of global observations of PM2.5 for epidemiological studies (Lary et al, 2014). Our bivariate results also indicated a positive association between GDP and lung cancer incidence illustrating the fact that rising affluence in developing countries may possibly be associated with an increase in smoking (Ezzati et al, 2005). Developing countries, moreover, now account for 80% of all smokers and lung cancer is projected to increase markedly in these countries (Mathers and Loncar, 2011;Murray, 1997;Tesfaye et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…A recent study has also demonstrated the potential of remote sensed and meteorological data products as being reliable representation of global observations of PM2.5 for epidemiological studies (Lary et al, 2014). Our bivariate results also indicated a positive association between GDP and lung cancer incidence illustrating the fact that rising affluence in developing countries may possibly be associated with an increase in smoking (Ezzati et al, 2005). Developing countries, moreover, now account for 80% of all smokers and lung cancer is projected to increase markedly in these countries (Mathers and Loncar, 2011;Murray, 1997;Tesfaye et al, 2007).…”
Section: Discussionsupporting
confidence: 70%
“…Given the overall low-SER of Arab towns, these findings can be explained by the fact that in poor communities where funds limit caloric intake, the more financial resources available, the more food and prepared industrial food they can obtain, and therefore the individual will have a higher chance of being overweight or obese [32] . It should be remembered that obesity has been called a disease of affluence, also because of this reason [40] . In this study wealth inequality was found to be negatively associated with adolescent overweight/obesity in Jewish towns, but not in the Arab towns.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of data from economically developing countries (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , we hypothesized that children from a…”
Section: Snacks Traditional Diet Food Patterns Nutrition Transitionmentioning
confidence: 99%